Financial management practices of small and medium enterprises in Nueva Ecija - Gallardo, Gaudencio P., Jr. (Animo Repository, 2017)
Small and Medium Enterprises (SMEs) play an important role in our economy as this sector contributes to the creation of wealth, employment and income generation. However, SMEs may be vulnerable to various challenges brought by competitive business environment. Among these, lack of an efficient and effective financial management system is a core problem area. This study determined the extent of financial management practices of SMEs in Nueva Ecija. Financial management was divided into three aspects: working capital management, capital budgeting, and financial reporting and analysis. Working capital management was determined in terms of cash management, account receivable management, and inventory management. In addition, the study ascertained if there were significant relationships between the organizational profile of SMEs and their financial management practices. Further, it was also determined if there were any significant differences in financial management practices among SMEs in terms of location and asset size. The respondents for this study were the SMEs located in the province of Nueva Ecija. The list of SMEs in Nueva Ecija was requested from the provincial office of Department of Trade and Industry, Cabanatuan City. From the list provided by DTI, a total of 172 SMEs were selected through stratified random sampling. The respondents were grouped into four based on the district where they operate. A five-point scale survey questionnaire was used in assessing the SMEs financial management practices. Results show that majority of SMEs in Nueva Ecija were sole proprietorship, engaged in retailing business, and considered as small based on asset size. Most of them were at their early years of operation which had at most 20 employees. Majority of the owners/managers were bachelors degree holder with average level of financial literacy. Cash management, account receivable management, inventory management as well as financial reporting and analysis were determined as highly practiced among SMEs. On the other hand, capital budgeting practices were assessed as moderately practiced. In addition, findings reveal that cash management practices were found to have a significant positive relationship with number of employees, level of education, and financial literacy of owner/manager. Both account receivable management and inventory management were found to have significant positive relationship with number of employees and level of education of owner/manager. Capital budgeting and financial reporting and analysis did not have significant relationships with any of the organizational characteristics. Further, results show that there were significant differences in financial management in terms of location and asset size. The findings provided an insight regarding the financial management practices among SMEs and these can be used by various organizations in providing technical assistance to continuously help the SMEs in improving their operations and overall performance.